RETRACTED: Identification of a Novel Ferroptosis Inducer for Gastric Cancer Treatment Using Drug Repurposing Strategy - Zhang, Jinping; Gao, Meimei; Niu, Ying; Sun, Jiangang (Frontiers in Molecular Biosciences, 2022)
Gastric cancer remains one of the major contributors to global cancer mortality, although there is no promising target drug in clinics. Hence, the identification of novel targeted drugs for gastric cancer is urgent. As a promising strategy for inducing ferroptosis for gastric cancer treatment, the ferroptosis inducer is a potential drug. Nevertheless, no ferroptosis inducer has entered clinics. So, our purpose was to identify a novel ferroptosis inducer for gastric cancer treatment using a drug repurposing strategy. Firstly, using a drug repurposing strategy with the aid of a commercialized compound library, HC-056456, a small molecule bioactive CatSper channel blocker, was characterized to inhibit the growth of gastric cancer line MGC-803. At the same time, this anti-proliferation effect can be blocked by ferrostatin-1, a ferroptosis inhibitor, indicating that HC-056456 is a ferroptosis inducer. Then, HC-056456 was identified to decrease GSH content via p53/SLC7A11 signaling pathway. Then Fe2+ and lipid peroxide were accumulated when cells were exposed to HC-056456. Finally, HC-056456 was found to suppress the growth of gastric cancer cells by increasing p53 and repressing SLC7A11 in vivo but not in the presence of ferrostatin-1. In sum, we systematically elucidate that HC-056456 exerts anti-gastric cancer effect by provoking ferroptosis in vitro and in vivo, suggesting its potential role in gastric cancer treatment.